An Alternative Wavelength Range for Noninvasive Assessment of Wound Tissue Oxygenation Status - P. Philimon, Sheena; K. C. Huong, Audrey; T. I. Ngu, Xavier (International Journal of Engineering and Technology, 2018)
This study aims to propose an alternative wavelength range for noninvasive prediction of wound transcutaneous blood oxygen saturation, StO2. A pilot study was undertaken on an injured subject with superficial wound on the palm of hand for consecutively seven days. The offline processing of the measured light signals revealed a considerable consistency in the mean and standard deviation of StO2 values calculated as Â and Â for the considered wavelength range of Â and , respectively. The average absolute mean difference was calculated as 5.72 %. This research concluded that Â range is suitably used in the prediction of wound StO2. The use of this range would significantly speed up data acquisition and collection process for the realization of real time imaging of skin oxygen level during different phases of wound healing.Â Â